The Influence Of Price And Product On Repurchase Intention At Pak Su's Grocery Store - Astri Djuraida; Sukardi Sukardi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to identify the influence of Price and Product on Repurchase Intention at Pak Su's Grocery Store. The research method used in this study adopts an associative approach, with purposive sampling as the sampling technique. The total number of respondents in this study is 100 consumers who have previously shopped at Pak Su's Grocery Store. The data analysis technique employed is multiple linear regression analysis using SPSS 25 software. The tests conducted in this study include validity testing, reliability testing, normality testing, linearity testing, and multicollinearity testing. Hypothesis testing is carried out using Simultaneous Testing (F-Test) and Partial Testing (t-Test). Based on the results of hypothesis testing, both simultaneously (F-Test) and partially (t-Test), it can be concluded that Price and Product have a positive and significant influence on Repurchase Intention. Additionally, both Price and Product independently have a positive and significant impact on Repurchase Intention.